AUTHORITY DISPUTE BETWEEN THE PARLIAMENT AND THE CONSTITUTIONAL COURT LAW NORMS IN FORMATION - Cahyowati, Rr; ., Kaharudin; Jayadi, Haeruman (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The purpose of this study was to determine the dispute of authority of state institutions that occurred between the Parliament and the Constitutional Court in the establishment of the rule of law level legislation , with specific targets in the form of teaching materials produced in the course of Constitutional Law and Technical Regulations . Moreover , the conflict is to be averted in the future state institutions , especially the Parliament and the Constitutional Court in the establishment of the rule of law level legislation . The research method used is a normative legal research, with the method of statute approach and methods of conceptual approaches . Approach through legislation that researchers will conduct in-depth study f the constitusional of the 1945 Constitution and the laws regarding the authority of state institutions in the establishment of the rule of law level legislation . Through a conceptual approach , researchers will examine the concepts of thought from the experts / Constitutional Law expert associated with the authority of state institutions in the formation of legal norms equivalent legislation in Indonesia . Based on research conducted found : a. The institution has the authority to make legal norms level legislation based NRI Constitution of 1945 is the House of Representatives . This is in accordance with the provisions of Article 20 paragraph ( 1 ) NRI Constitution of 1945 which determines the